Associating prenatal phthalate exposure with childhood autistic traits: Investigating potential adverse outcome pathways and the modifying effects of maternal vitamin D - Hui Gao; Cheng Zhang; Beibei Zhu; Menglong Geng; Juan Tong; Zixiang Zhan; Yi Zhang; De Wu; Kun Huang; Fangbiao Tao (Eco-Environment & Health)
The association between prenatal phthalate mixture exposure and the risk of autism spectrum disorder (ASD) in children, as well as the potential mechanism and impact of maternal vitamin D, remains unclear. We analyzed data from 3209 mother–child pairs. The associations between prenatal phthalate exposure and autistic traits in children aged 1.5, 3, 5, and 6 years were explored. Furthermore, the modifying effects of maternal vitamin D and the adverse outcome pathway, which elucidates the contribution of phthalates to ASD, were estimated. Exposure to a phthalate mixture was associated with an increased risk of ASD in children aged 1.5–6 years. For mothers with 25(OH)D deficiency, an exposure‒response relationship was observed between phthalate mixtures in early to mid-pregnancy and autistic traits in children aged 3 years. However, this association was not observed for mothers with sufficient prenatal 25(OH)D levels. The potential mechanism of action of di(2-ethylhexyl) phthalate (DEHP) exposure may involve affecting GRIN2B, inhibiting NMDAR in the postsynaptic membrane, disrupting synaptic function, and impairing learning and memory, ultimately leading to ASD development. Importantly, maternal vitamin D supplementation was demonstrated to mitigate the risk of ASD associated with phthalate exposure. Reducing phthalate exposure during pregnancy may be associated with a decreased risk of autistic traits in children. Furthermore, adequate vitamin D supplementation could potentially mitigate the impact of phthalates on these traits. Additionally, the proposed biological mechanism provides insight into how phthalate exposure may contribute to the development of ASD.